Spontaneous streptomycin resistance and efficiency of Rhizobium strains native in Brazilian cerrados associated with Stylosanthes - Sá, Nadja M. H.; Scotti, Maria Rita M. L.; Vargas, Milton A. T.; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
Rhizobium strains were isolated from nodules of Stylosanthes spp. in undisturbed or cultivated Cerrado soils that have never been inoculated, in order to study the nature of the factors that affect stablishment of Rhizobium strains introduced in these soils, as well as to evaluate the N2 fixing capacity of the native strains. Streptomycin resistance level of the Rhizobium strains were tested in yeast-mannitol-agar plates. Among 122 strains isolated in cultivated Cerrado, 35% were resistant to concentrations equal or above 40 μg/ml, while only 10% within 92 strains isolated in undisturbed Cerrados were resistant to that level. These data suggest that the ecological changes caused by cultivation of virgin savanna land result in competitive advantages for Streptomycin resistent Rhizobium strains. Experiments carried out in Leonard jar assemblies with san and sterilized solution indicated that 61% of the strains isolated in S. guianensis var. Canescens and S. grandifolia were low or moderately effective in the homologous host, while only 14% of the strains had a high level of N2 fixation. This low percentage of efficient strains suggests the necessity of a Rhizobium strain selection program adapted to the Cerrado conditions, aiming to obtain high quality inoculant for the Cerrados region.